Hubungan Stres Kerja dengan Kelelahan Kerja Petani Karet di PTPN XII Kebun Renteng-Ajung Jember - Sari Mulia Ningrum; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Rubber farmers often face heavy workload problems, cold weather, and unsafe environmental conditions that cause job stress and work fatigue. The study aimed to analyze the relationship between job stress and work fatigue of rubber farmers. The study design used observational analytic research with cross sectional approach and used the sampling technique using simple random sampling, resulting in 78 respondents. Data collection used the job stress questionnaire and the Fatigue Severity Scale (FSS). Data analysis was performed by Spearman-rank Correlation test with a significance level of 0.05 there is a relationship between job stress and work fatigue. The results showed that from 78 respondents, there were 73 respondents (92.6%), meaning farmers experienced high stress. And as many as 78 respondents (100%) experienced high work fatigue. There is a significant relationship between job stress and work fatigue rubber farmers in PTPN XII Renteng Plantation, Ajung, Jember Regency (p-value 0,000; r = 0.538) have a positive relationship or the higher job stress, the higher work fatigue. Farmers can do relaxation therapy to prevent the occurrence of work stress so that it does not cause work fatigue.